Bayou dogs - Abbott, Tony, 1952- (Abbott, Tony, 1952- Haunting of Derek Stone, 2009)
Could the road to the afterlife be a two-way street? Derek's brother Ronny isn't himself. No, really. Ronny's body has been taken over by the long-dead soul of a man named Virgil Black. Lucky for him, Virgil is one of the good guys. Not all of them are. In fact, a Legion of evil souls is staging a serious comeback. And they're staging it at Bayou Malpierre, the site of Derek's most horrible nightmare. That nightmare is about to get even worse. . . .